Prevalence of Extended-Spectrum β-Lactamases in Multidrug-Resistant Klebsiella pneumoniae Isolates in Jordanian Hospitals - Suhaila A. Al-Sheboul; Ghina S. Al-Madi; Brent Brown; Wail A. Hayajneh (Springer, 2023)
Abstract The increase in the prevalence of infections caused by certain bacteria, such as Klebsiella pneumonia (K. pneumoniae), is a global health concern. Bacterial production of an enzyme called extended-spectrum beta-lactamase (ESBL) can generate resistance to antimicrobial therapeutics. Therefore, between 2012 and 2013, we investigated K. pneumoniae that produce ESBLs with the prevalence of individual genes including bla SHV, bla CTX-M, bla TEM, and bla OXA isolated from clinical samples. A total of 99 variable diagnostic samples including blood from hematological malignancies (n = 14) or other clinical sources including sputum, pus, urine, and wound (n = 85) were analyzed. All samples' bacterial type was confirmed and their susceptibility to antimicrobial agents was established. Polymerase chain reaction (PCR) amplification was carried out to ascertain presence of specific genes that included bla SHV, bla CTX-M, bla TEM, and bla OXA. Plasmid DNA profiles were determined to assess significance between resistance to antimicrobial agents and plasmid number. It was found that among non-hematologic malignancy isolates, the highest rate of resistance was 87.9% to imipenem, with lowest rate being 2% to ampicillin. However, in hematologic malignancy isolates, the highest microbial resistance was 92.9% to ampicillin with the lowest rate of resistance at 28.6% to imipenem. Among collected isolates, 45% were ESBL-producers with 50% occurrence in hematologic malignancy individuals that were ESBL-producers. Within ESBL-producing isolates from hematologic malignancy individuals, bla SHV was detected in 100%, bla CTX-M in 85.7%, and bla TEM and bla OXA-1 at 57.1% and 27.1%, respectively. In addition, bla SHV, bla CTX-M, and bla OXA were found in all non-hematological malignancy individuals with bla TEM detected in 55.5% of samples. Our findings indicate that ESBLs expressing bla SHV and bla CTX-M genes are significantly prevalent in K. pneumoniae isolates from hematologic malignancy individuals. Plasmid analysis indicated plasmids in isolates collected from hematological malignancy individuals. Furthermore, there was a correlation between resistance to antimicrobial agents and plasmids within two groups analyzed. This study indicates an increase in incidence of K. pneumoniae infections displaying ESBL phenotypes in Jordan.